5G-band millimeter wave patch array antenna - Wang, Wenhao (Nanyang Technological University, 2022)
With the development of 5G technology, antennas, as a vital component of 5Gsignal transmitting equipment, are widely used in communication, radar, navigation, and other fields. Due to the development of many emerging fields based on 5Gtechnology, the requirements for antenna performance are increasingly high, which has become an important research direction in the field of antennas at home and abroad. In this report, according to the requirements of the above commercial applications for antennas, on the basis of relevant theories and closely combined with scientific research projects, the research and design of high-gain array antenna are carried out. The main work is as follows: Firstly, according to the relevant indicators of commercial 5G, the spacing and number of array units are determined. Considering the sidelobe level and the practicability of the feed network, the topology of the feed network is determined on the basis of the array excitation distribution, and a 4x4 T junction microstrip line power division network is designed based on quarter impedance converter. HFSS electromagnetic simulation is used to verify that the network has good impedance matching and transmission characteristics. Finally, the whole structure of the array is simulated and optimized based on each part. The test results show that when the dielectric constant is 2.2, the array gain reaches 20dB and the sidelobe level is less than -13dB, which meets the requirements of the index. Keyword: Array antenna, Microstrip patch antenna, HFSS, High performance feed network